Academic success strategy use among community-active urban Hispanic adolescents. - Vick RM; Packard BW (Hispanic Journal of Behavioral Sciences, 2008)
Although much has been written about the 'risky' behaviors in which some Hispanic adolescents participate, the predictors of academic success are less understood. Toward this end, predictors of academic self-regulation were investigated in Hispanic adolescents. Specifically, a predictive model incorporating self-efficacy, instrumentality, salience of becoming a college student, and structured programming was examined in a sample of 66 Hispanic teens drawn from an urban community center. A model including self-efficacy, instrumentality, and salience of becoming a college student explained 53% of the variance in academic self-regulation, and further regression tests suggested that self-efficacy acted as a mediator of the other two predictors. However, structured leadership programming was not related to self-regulation. Case illustrations are presented. Future research involving the study of community-active Hispanic teens and their academic success is discussed.